Hubungan Self-Efficacy dan Motivasi dengan Self-Management pada Penderita Hipertensi - Putri, Shelsa Aprilia; Tauriana, S; Nugroho, Setiyo Adi (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Hypertension is one of the most prevalent chronic diseases and a major risk factor for severe complications such as stroke, kidney failure, and cardiovascular disorders. Its management requires long-term strategies that go beyond pharmacological treatment and rely heavily on patients’ ability to engage in effective self-management. However, low levels of self-efficacy and motivation often hinder patients’ adherence to treatment regimens and lifestyle modifications. This study aimed to examine the relationship between self-efficacy, motivation, and self-management among hypertensive patients. An observational analytic design with a cross-sectional approach was applied, involving 163 respondents recruited through total sampling. Data were collected using the General Self Efficacy Scale (GSES), the Treatment Self Regulation Questionnaire (TSRQ), and the Hypertension Self Management Behavior Questionnaire (HSMBQ). Statistical analysis was conducted using Spearman’s correlation test. The findings revealed significant relationships between self-efficacy and self-management (p=0.003) and between motivation and self-management (p=0.005). These results emphasize that enhancing patients’ psychological empowerment and motivation is essential for successful self-management of hypertension. The study suggests that comprehensive interventions integrating health education, family support, and motivational strategies are needed to strengthen patients’ adherence to healthy lifestyles and treatment regimens. By addressing these psychological and behavioral aspects, healthcare providers can help reduce the risk of complications and improve patients’ overall quality of life. Consequently, this research provides valuable insights and a scientific basis for designing more effective primary care interventions targeting hypertensive populations.